Say it again, Sam a literary and filmic study of narrative repetition in 1 Samuel 28 - Kent, Grenville J. R. (Eugene, Or. : Pickwick Publications, 2011)
This book offers a synchronic exegesis of Saul's night visit to the witch of En-dor (1 Samuel 28:3-25), focusing on the web of repetitions of visual elements, of symbols, of sounds, of entire scenes, and of keywords. Kent shows how an artistry of repetition and non-repetition helps to build characterization, plot, structure, as well as prophetic fulfillments, foreshadowing, and inter-textual warnings. He also argues that film theory applied to the analysis of story in the Hebrew Bible helps us attain much greater clarity in our appreciation of the functions of narrative repetition.
Repetition in biblical narrative -- Repetition in literary theory -- Forms and effects of repetition in film theory -- 1 Samuel 28 in biblical studies research -- Exegesis of 1 Samuel 28.
Includes bibliographical references (pages 223-238) and indexes.
Description based on print version record.
Keywords: Bible. -- Criticism, Narrative; Repetition (Rhetoric); Narration in the Bible; Film criticism; RELIGION / Biblical Studies / Old Testament; Electronic books